The occupation of university professors and salary remuneration: Case of the professors of the School of Library, Documentation and Information of the National University of Costa Rica. - Valverde, Marjorie Mora (2007)
This article shows the principal results of a wide research on the salaries about professionals workers in bibliotecology, I is a motive of worry of the authorities of Bibliotecology's School, Documentation and Information of the National University from the process of autoevaluation, realized before the accreditation of Bibliotecology's career and Documentation from the part of the National System of Accreditation of the high Education (SINAES). This research has demonstrated the inequity salaries that affect the teacher of the National University, in relation to the salaries of the teachers of other schools of bibliotecology and, also, to the personnel that occupies administrative positions both in the same National University and in the public sector. The low salaries of the teachers and the lack of economic incentives in a fundamental function for an institution of higher education, not only is a motive of protest for the personal, due to they are responsible for a hard load of labour in an accredited school, but also represents on obstacle to contract highly qualified teachers